Tissue buccal fat pad–stromal vascular fraction as a safe source in maxillofacial bone regeneration: A clinical pilot study. (April 2023) - Bohlouli, Mahboubeh; Bastami, Fashid; Nokhbatolfoghahei, Hanieh; Khojasteh, Arash
Summary: Aim: The purpose of this study was to examine the biological properties of the buccal fat pad (BFP)-derived tissue stromal vascular fraction (tSVF) in vitro and compare them with BFP-derived cellular SVF (cSVF). Furthermore, a clinical pilot study assessed the safety of using BFP-derived tSVF for maxillofacial bone regeneration. Materials and methods: This study was performed in two sections: 1) experimental section: BFP tissue was harvested from three healthy donors, and then cSVF and tSVF were isolated by enzymatic and mechanical methods to assess their biological properties and 2) clinical section: Ten patients with maxillofacial bone defects were enrolled according to eligibility criteria and offered two options for surgery, including autologous BFP-tSVF (n = 5) and autologous bone grafting (n = 5), to evaluate safety after a year of follow-up. Results: The BFP-tSVF exhibited high cell viability and various cell surface markers, including CD45, CD31, and CD34. There was no population-doubling time and multilineage differentiation capacity compared with BFP-cSVF. BFP-tSVF is safe because of the lack of intervention-related adverse events reported in donor and surgery sites during a one-year period. In addition, cell therapy was feasible because it can be performed during surgery and requires little preparation time. Patients in the ABG group experienced pain and tenderness in the iliac crest, leading to dissatisfaction and complications. Conclusion: The experimental results confirmed that the cells isolated from BFP-tSVF have stemness properties similar to BFP-cSVF. Clinical evaluation also indicated that this cellular product could be used safely to regenerate maxillofacial bone defects.